Internal Financial Capacity and Investment Intensity: The Moderating Role Of Cash Holdings - Gun Gun Budiarsyah; Mutty Claudia Dewinda; Mandasari. R (Jurnal Ekuilnomi, 2026)
This study examines how profitability, leverage, liquidity, and firm size affect investment intensity, with particular emphasis on the moderating role of cash holdings. Using panel data from firms listed on the Indonesia Stock Exchange over 2000–2024, the analysis employs fixed-effects regression with robust standard errors. The results show that profitability and firm size are positively associated with investment intensity, whereas leverage and liquidity exert negative effects. More importantly, cash holdings significantly moderate these relationships by strengthening the positive effect of profitability and mitigating the negative effects of leverage and liquidity, highlighting the role of internal liquidity as a financial buffer. Additional analyses using asset tangibility and cash flow as alternative moderators confirm the robustness of the main findings. Asset tangibility provides the strongest and most consistent moderating effects, while cash flow offers supportive but more selective evidence. Overall, the findings suggest that investment intensity depends not only on firm fundamentals but also on firms’ internal financial capacity